Mexico : Review Under the Flexible Credit Line Arrangement-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses Mexico's Review Under the Flexible Credit Line (FCL) Arrangement. Mexico has navigated successfully a complex external environment, characterized by falling commodity prices, a sharp appreciation of the U.S. dollar, and heightened volatility in international financial markets. The economy continues to grow at a moderate rate and inflation is close to the target. Looking ahead, activity should be supported by strengthening external demand and by the implementation of the structural reforms. The IMF staff's assessment is that Mexico continues to meet the qualification criteria for access to FCL resources.